Plant Virus Transport Function: Complementation by Helper Viruses Is Non-specific - Malyshenko, S. I.; Kondakova, O. A.; Taliansky, M. E.; Atabekov*, J. G. (Journal of General Virology, 1989)
SUMMARY The possibility of complementation of the cell-to-cell spread (within the inoculated leaf) between different related and unrelated plant viruses has been studied. Various tobamoviruses (tobacco mosaic, sunn-hemp mosaic, cucumber green mottle mosaic viruses and ‘tobamovirus from orchids’) can facilitate each other’s replication in non-permissive hosts or at a temperature non-permissive for transport of one of the virus partners, probably by complementation of transport functions. Complementation of movement also occurred between some, but not all unrelated viruses tested. The complementation in transport function seems to be non-specific: it can occur between viruses even if their putative transport proteins significantly differ in structure. Consequently these viruses were classified tentatively into different ‘transport groups’.
Keywords: tobamovirus